Business Students’ Perceptions of Employability Skills: An Exploratory Study in Saudi Arabia - Maher ABOU HAMAD; Yousif ABDELRAHIM (Communications of International Proceedings, 2024)
In light of the increasing changes in the global economic context, research has indicated that educational institutions and the job market are facing many challenges, one being the required employability skills of graduates upon recruitment. This study aimed to explore undergraduate business students’ perceptions as to the extent to which they agree certain employability skills important for job recruitment.  The research method was a quantitative and qualitative one with 123 business students participating in a questionnaire and 20 participants in a semi-structured interview in one university in Saudi Arabia. Main findings indicated that the participants considered all the mentioned employability skills highly important according to the students’ university year or choice of future job but there were no significant differences.  However, Sophomore level students showed a high positive significant difference in considering leadership as the most important skill over their junior and senior year counterparts.  The findings further indicated that although the participants found the communication and leadership skills more important than the other skills, life-long learning, tolerance and language, considered of high importance in the research literature, were viewed not as important. Further, the interview responses indicated insufficient knowledge of how to develop their own skills to meet the market needs and sustainable employment. Implications of the present study show that there is a need for urgent collaboration between the educational institution and the job market to identify the required employability skills.  Future research on matching stakeholders’ employability skills is recommended.
Keywords: Employability; Higher Education; Perceptions; Generic Skills; Saudi Arabia